The Influence of Communication and Work Discipline of Doctors on Loyalty Mediated by Patient Satisfaction at the Pediatric Polyclinic of RSHMCB - Wijaya, Arry; TJ, Hery Winoto; Saparso (ID Solutions, 2025)
The decline in patient visits at the Pediatric Polyclinic of RSHMCB is influenced by issues related to doctor communication and discipline. This study aims to examine the effect of doctor communication and discipline on patient loyalty, with patient satisfaction as a mediating variable. To analyze the effect of doctor communication and discipline on patient loyalty, with satisfaction as a mediator. This study uses a quantitative survey approach with 95 respondents. Data were collected using questionnaires and analyzed with Partial Least Square (PLS). Doctor communication significantly affects loyalty (p = 0.000) and patient satisfaction (p = 0.028). Discipline significantly affects satisfaction (p = 0.000) but does not directly affect loyalty (p = 0.922). Patient satisfaction mediates the relationship between discipline and loyalty (p = 0.027). Doctor communication and discipline affect patient satisfaction, which in turn increases patient loyalty. Hospitals should improve doctor communication and discipline to enhance patient loyalty